Kosani's Method in Classification of Fiqh - Qambarov A’zam Muxammadali o‘g‘li (Scientific Trends, 2025)
This study provides a comprehensive examination of the Kosanis Method as an emerging framework for the classification of fiqh within Islamic jurisprudence. Traditional systems of fiqh classification, shaped by early Islamic scholars and developed through the evolution of the madhāhib, often rely on rigid thematic and doctrinal divisions. The Kosanis Method advances beyond these classical models by offering a more systematic, context-sensitive, and interdisciplinary approach to organizing legal principles. This method integrates historical trajectories, socio-cultural conditions, legal maxims (al-qawāʿid al-fiqhiyyah), and contemporary legal needs, thereby enabling a more dynamic interpretation of Islamic law. Through analysis of its core principles—including contextualization, adaptability, and cross-disciplinary alignment—the study illustrates how the Kosanis Method facilitates clearer categorization of rulings in areas such as muʿāmalāt, ʿibādāt, family law, and Islamic finance. Case studies, including applications of hybrid fuzzy inference systems in determining child alimony, demonstrate the method’s potential for practical implementation in modern judicial processes. The research concludes that the Kosanis Method significantly enriches contemporary fiqh scholarship by reconciling classical jurisprudential heritage with the demands of modern legal systems, offering a promising paradigm for future developments in Islamic legal theory and applied jurisprudence.
Keywords: Fiqh Classification, Kosanis Method, Islamic Jurisprudence, Legal Maxims (al-Qawāʿid al-Fiqhiyyah), Contextual Legal Analysis, Islamic legal methodology.